(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the article, the formation of types of scientific cognition, especially epistemic cognition among students is considered as an example of problems related to the analysis of the movement of a point charge in the electric field of uniformly charged bodies of finite size. In addition, integration was used to calculate the electric field strength of charged bodies, and by integrating it over different intervals, it was shown to obtain information about the trajectory of the field force lines consisting of broken lines and, accordingly, the trajectory of the point charge. It is proposed that the solving of these types of problems helps students to acquire epistemic knowledge and develop creativity by applying it.